Freedom to learn–independent campus policy: Do we really find our freedom? - Rossalina Christanti; Andreas Ari Sukoco (Journal of Education and Learning (EduLearn), 2022)
What the job market demanded in the last few decades is overwhelming. Universities are working hard to meet the quality required by the job markets and it took a lot of effort, physically and mentally. Recently, the Minister of Education and Culture Republic of Indonesia releases a policy that opens up the door to unlimited resources of learning. Students will be facilitated to choose their learning sources from outside the classroom, with real professionals. It is hoped that the quality of education in Indonesia will be enhanced and universities can produce graduates who have competencies that are relevant to the needs of industry, business, and the world of work. This research mainly reviews the Freedom to Learn–Independent Campus (FLIC) policy as an opportunity to conduct independent learning. Independent to choose the more contextual source of learning. Our study context is the implementation of the FLIC program specifically at the School of Business. The researchers conducted interviews with stakeholders related to the implementation of this policy (students, faculty members, co-educators). As a result, FLIC is perceived to have a positive impact on improving student abilities. However, there are still some obstacles that can be used as a basis for policy improvement.